The Role of Digital Capabilities in Enhancing Customer Satisfaction through Product Quality and Service Quality. - Ikbal Anggara; amalia amalia (INKOFAR, 2026)
Background The increasing competition in the fashion industry requires companies to continuously improve their capabilities to maintain customer satisfaction. In this context, digital capabilities have become an important factor that supports firms in improving product and service performance Purpose This study aims to examine the role of digital capabilities in enhancing customer satisfaction through product quality and service quality in the context of local sport fashion brands in Indonesia Methodology The study employs a quantitative approach using data collected from 100 respondents who have experience purchasing products from local sport fashion brands. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings The results indicate that digital capabilities have a significant positive effect on both product quality and service quality. Furthermore, product quality and service quality significantly influence customer satisfaction. Implications The findings also reveal that digital capabilities indirectly enhance customer satisfaction through improvements in product and service quality. These results highlight the importance of integrating digital technologies into business processes to improve product performance and service responsiveness. Originality The study provides practical implications for local sport fashion brands to strengthen their digital capabilities in order to enhance customer satisfaction and maintain competitiveness in the market.